PENGARUH PENERIMAAN PAJAK HIBURAN DAN INFLASI TERHADAP PENDAPATAN ASLI DAERAH : Studi Kasus Pada Badan Pendapatan Daerah Kabupaten Ende - Deno, Agustina; Djou, Laurentius D Gadi; Ismail, Nuraini (Program Studi Akuntansi Universitas Flores, 2021)
The purpose of this study is to determine (1) To determine the effect of entertainment tax revenue on Regional Original Revenues. (2) To find out inflation affects the Regional Original Revenue. Analysis of the data used is multiple linear regression analysis. To facilitate analysis, the Statistical Package for the Social Sciens (SPSS) program for windows is used. The results of this study indicate that the results of the t test of entertainment tax variables obtained tcount> ttable where 4.801> 2.353 and the significance value obtained was 0.041 <0.05. Thus it means that partially the entertainment tax revenue variable has a significant effect on the PAD variable in the Ende Regency Revenue Agency. The t-test results of the inflation variable obtained value of t> t table where 16.026> 2.353 and the significance value obtained was 0.004 <0.05. Thus it means that partially the inflation variable has a significant effect on the PAD variable in the Ende Regency Regional Revenue Agency.